Phenomenology of AdS/QCD and its gravity dual - Galow, Benjamin; Megías Fernández, Eugenio; Nian, Jun; Pirner, Hans J. (Nuclear physics. B, Particle physics, 2010)
We construct the dilaton potential in the gravity dual theory of AdS/QCD for the warp factor of Pirner and Galow [1] and Nian and Pirner [2]. Using this AdS5-metric with properties similar to QCD, we find that the gravity dual leads to a meaningful gauge coupling in the region between the charmonium and bottonium mass, but differs slightly from QCD in the extreme UV. When we fix the ultraviolet behavior in accord with the β-function, we can obtain good agreement with the overall heavy quark-antiquark potential. Although the leading order proportional to −α4/3r differs from perturbative QCD, the full potential agrees quite well with the short distance QCD potential in NNLO.